Titin: roles in cardiac function and diseases - Stroik, Dawson; Gregorich, Zachery R.; Raza, Farhan; Ge, Ying; Guo, Wei (Frontiers in Physiology, 2024)
The giant protein titin is an essential component of muscle sarcomeres. A single titin molecule spans half a sarcomere and mediates diverse functions along its length by virtue of its unique domains. The A-band of titin functions as a molecular blueprint that defines the length of the thick filaments, the I-band constitutes a molecular spring that determines cell-based passive stiffness, and various domains, including the Z-disk, I-band, and M-line, serve as scaffolds for stretchsensing signaling pathways that mediate mechanotransduction. This review aims to discuss recent insights into titin's functional roles and their relationship to cardiac function. The role of titin in heart diseases, such as dilated cardiomyopathy and heart failure with preserved ejection fraction, as well as its potential as a therapeutic target, is also discussed.